“Liturgia ex machina?!” – Practical Theological Reflections on the Use of Artificial Intelligence and Technology in Liturgical Celebrations - Chrostowski, Mariusz; Siegert, Julia Maria (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
This article aims to theoretically analyse the use of artificial intelligence (AI) and technology in liturgical events (liturgia ex machina). To this end, the first section outlines a hermeneutical horizon that encompasses the meaning and transformation of liturgy in the age of digitalisation and technologization. Building on this, the second section initiates a reflection on AI and technology in the liturgy, dealing with the limits and potentials involved. These relate on the one hand to the forms of the liturgy (sacraments and sacramentals) and on the other to its factors (e.g. acoustic, visual, temporal and spatial). Finally, the main conclusions and prospects for using AI and modern technology in the liturgy are outlined.